2014
DOI: 10.1002/hed.23613
|View full text |Cite
|
Sign up to set email alerts
|

Dissection and identification of parathyroid glands during thyroidectomy: Association with hypocalcemia

Abstract: Identification of a higher number of parathyroid glands is associated with a higher incidence of postoperative temporary hypocalcemia and permanent hypoparathyroidism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 27 publications
(61 reference statements)
3
41
2
1
Order By: Relevance
“…Previous studies have variably identified younger age [14, 19, 23], female sex [4, 9, 14], Hashimoto thyroiditis [18, 22], and malignancy [13, 15, 16, 19, 23, 30] as potential risk factors for IPT. Of notice, Sakorafas and Gourgiotis reported lower rates of IPT in patients with malignancy, owing probably to more meticulous dissection in cases of suspected malignancy [4, 10].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have variably identified younger age [14, 19, 23], female sex [4, 9, 14], Hashimoto thyroiditis [18, 22], and malignancy [13, 15, 16, 19, 23, 30] as potential risk factors for IPT. Of notice, Sakorafas and Gourgiotis reported lower rates of IPT in patients with malignancy, owing probably to more meticulous dissection in cases of suspected malignancy [4, 10].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the effort for this cause increases the possibility of postoperative transient hypocalcemia (28,29). Ideally, these glands should be preserved in their place without compromising vascularization.…”
Section: Discussionmentioning
confidence: 99%
“…Some papers have suggested the use of these devices may have an effect on parathyroid function, although no conclusive papers were found to date [18]. Intraoperative factors that have been shown in some series to be associated with increased risk of hypocalcaemia include: number of parathyroids identifies; parathyroids removed; autotransplantation of parathyroid tissue; and longer operative time [4,8,12,14]. Autotransplantation in particular is controversial with recently published papers suggesting it is either protective for parathyroid function or futile [12,19,20].…”
Section: Factors Not Included In the Analysismentioning
confidence: 94%